Multivariable Analysis of Thesis Completion Procrastination: Evaluating Personal Traits, Campus Services, and Academic Stress - Noer Hidayah; Ika Insyiroh; Novi Rosita Rahmawati; Marwa Mansour (Pedagogy Review, 2026)
This study investigates the complex determinants of academic procrastination in thesis completion, specifically examining the roles of academic stress, campus services, perfectionism, and self-regulation, with gender as a moderating variable. While university support is traditionally viewed as a mitigating factor in procrastination, empirical evidence on its interaction with gender-specific psychological traits remains underdeveloped. This study employs a quantitative research design utilizing Moderated Regression Analysis (MRA) to examine the hypothesized relationships. Data analysis was conducted using the R statistical software with the lm package for linear modeling. The target population consisted of undergraduate students currently in the final phase of their thesis completion. A total of 115 respondents participated in the study, comprising the primary data set for the analysis.  Bootstrapped regression analysis revealed that academic stress was the sole robust positive predictor of thesis procrastination . Gender emerged as a pivotal moderator, with a significant interaction confirmed between perfectionism and gender . Perfectionism operates as an adaptive motivational force for male students but shifts into a maladaptive trait among functions as an adaptive motivational force for male students but becomes a maladaptive trait for females. Furthermore, a marginally significant interaction was observed between self-regulation and gender  suggesting a tendency for self-regulation to mitigate procrastination more pronouncedly among female students. Conversely, the direct effects of campus services proved statistically unreliable under the bootstrap framework. Thesis procrastination is not merely a reflection of time-management deficits or direct environmental influences, but a situational emotional response to chronic academic stress bounded by gender-specific psychological mechanisms. In practice, the findings imply that higher education institutions must move beyond generic academic support or physical facility enhancements. Universities and thesis advisors should prioritize dismantling structural stressors in the supervision workflow while implementing gender-aware psychological interventions to mitigate maladaptive perfectionism and foster self-compassion among female students. Keywords: Thesis completion, procrastination, perfectionism, self-regulation, academic stress, and campus service